PF-12 Colectomy by Rectal- Pull Through Technique for Colonic Tumor in Eight Years Old Dog - Siti Zaenab; Osye Alamsari; Eva Zulfiati; Tri Cahyo Dirgahariyawan (Hemera Zoa, 2018)
Dogs are one of those independent carnivores. However, dogs are also susceptible to digestion disease. In addition to diarrhea, obstruction or constipation, diseases that can also interfere with the digestive system are tumors of the digestive tract. Guyton, 2005).Tumor or neoplasm disease is one of the most important medical problems for immediate treatment. The cause of tumor is very varied and very complex (Tjarta, 2002). Percentage incidence of tumor disease in animals, especially dogs is quite high. Until now, the prevention of tumor disease is generally done by surgery, radiation and chemotherapy.